A comparison of antifibrillatory drugs in the heart-lung preparation - Rand, M. J. (1958)
Quinidine, amethocaine, Trasentin and atropine have been tested for their ability to stop atrial fibrillation produced in the heart-lung preparation of the dog by stimulating the right atrium in the presence of acetylcholine. The results suggest that atropine acts by specifically antagonizing acetylcholine, but that amethocaine and Trasentin act chiefly by virtue of their quinidine-like properties.